Inadequate Cryptocurrency and Money Laundering Regulations in Indonesia (Comparative Law of US and Germany) - Putri, Tiara; Amiludin, Amiludin; Ahmad, Dwi Nurfauziah; Hidayatulloh, Hidayatulloh (Yustisia, 2023)
Cryptocurrency as a virtual currency managed by a decentralized system makes it immune to government interference and allows it to transact under pseudonyms. This has the potential for cybercrime and illicit transactions, especially money laundering. This study aims to compare legal instruments in Indonesia, the US, and Germany regarding the use of cryptocurrency as a money laundering tool and to analyze the readiness of Indonesia to respond to this crime. This study is normative legal research conducted using a comparative and statutory approach. These findings show that the US and Germany have extensively regulated crypto. In the US, Crypto transactions are considered MSB, subject to BSA compliance. Each transaction must comply with AML, KYC, and CIP requirements. In Germany, Cryptocurrency is considered a personal asset. The crypto trading must meet the KYC and AML requirements. Indonesia needs advanced regulations because crypto is only considered an investment asset. The investigation is difficult because cryptocurrency is transacted pseudonyms, so connecting pseudonyms with real people is challenging